A Rapid Neurological Assessment Protocol for Repeated Mild Traumatic Brain Injury in Awake Rats. Issue 1 (19th July 2019) - Christie, Brian R.; Trivino‐Paredes, Juan; Pinar, Cristina; Neale, Katie J.; Meconi, Alicia; Reid, Hannah; Hutton, Craig P.
Abstract: Preclinical models for mild traumatic brain injury (mTBI) need to recapitulate several essential clinical features associated with mTBI, including a lack of significant neuropathology and the onset of neurocognitive symptoms normally associated with mTBI. Here we show how to establish a protocol for reliably and repeatedly inducing a mild awake closed head injury (ACHI) in rats, with no mortality or clinical indications of persistent pain. Moreover, we implement a new rapid neurological assessment protocol (NAP) that can be completely conducted within 1 min of each impact. This ACHI model will help to rectify the paucity of data on how repeated mTBI (r‐mTBI) impacts the juvenile brain, an area of significant concern in clinical populations where there is evidence that behavioral sequelae following injury can be more persistent in juveniles. In addition, the ACHI model can help determine if r‐mTBI early in life can predispose the brain to exhibiting greater neuropathology (i.e., chronic traumatic encephalopathy) later in life and can facilitate the identification of critical periods of vulnerability to r‐mTBI across the lifespan. This article describes the protocol for administering an awake closed head mTBI (i.e., ACHI) to rats, as well as how to perform a rapid NAP following each ACHI. Methods for administering the ACHI to individual subjects repeatedly are described, as are the methods and scoring system for the NAP. The goal of this article is to provide a standardized set of procedures allowing the ACHI and NAP protocols to be used reliably by different laboratories. © 2019 by John Wiley & Sons, Inc.